The Impact of Forest Bathing (Shinrin-Yoku) on Adolescent Mental Health: A Systematic Review of Existing Evidence - Firmansyah, Deni; Albianto, Deranito Langlang Paresa; Nurpadilah, Demita; Purwati, Ayu Endang; Firmansyah, Andan; Setiawan, Henri (Genius Journal, 2025)
Introduction: Shinrin-yoku, or forest bathing, is a natural therapy method that involves direct interaction with the forest environment and is associated with various mental health benefits. This study aims to systematically evaluate the impact of forest bathing on adolescent mental health by analyzing the available scientific evidence. Objective: This study aims to systematically analyze the impact of forest bathing (shinrin-yoku) on adolescent mental health. Method: A systematic search was conducted in the PubMed, ProQuest, JSTOR, and Garuda databases from 2017 to 2024, focusing on adolescent populations experiencing mental health disorders such as anxiety, depression, and low self-esteem, without restrictions on gender, religion, or race. Result: Seven studies involving a total of 245 participants were analyzed. Forest bathing (Shinrin-yoku) consistently demonstrated significant benefits in reducing symptoms of depression and anxiety while enhancing overall mental well-being. The intervention cycles ranged from one day to five months, with session durations varying between 40 minutes and four hours. These sessions included structured activities in forest environments, such as walking, meditation, and inhaling forest air, either dynamically or statically Conclusion: Forest bathing (Shinrin-yoku) is effective in improving adolescent mental health by reducing anxiety and depression while enhancing psychological well-being. The clinical implications for nursing practice include integrating forest bathing as a non-pharmacological intervention in holistic care, particularly in community and school settings, to support stress management and prevent mental health issues among adolescents.